Analisa kinerja bongkar muat dengan lean six sigma untuk mengurangi demurrage di pelabuhan PT. Petrokimia Gresik - Ni’matus Syajarotul Aliyah; Yugowati Praharsi; Danis Maulana (Universitas Kristen Maranatha, 2020)
PT. Petrochemical Gresik is one of the firms that has a terminal to be operated by own company (Terminal for Self-interest / TUKS) which supports the activity of unloading raw materials for production and loading activities to load production results. However, in carrying out its operational activities, it still causes demurrage which is a penalty that must be paid by the shipper to shipowner because it exceeds the time limit agreed in the contract of the ship. In this study, an analysis will be carried out on how to identify waste, analyze the causes of waste in the loading and unloading performance of the ship, and analyze how to minimize the factors causing demurrage in TUKS PT. Petrochemical Gresik. The research method used is lean six sigma by integrating the concept of lean process (7 waste) to the six sigma tools namely DMAIC (Define, Measure, Analyze, Improve, and Control). The results of the research at the define phase can be identified into twenty-one CTQ (Critical to Quality) with the highest waste value, namely the internal equipment breakdown category which will only be analyzed further. Subsequently, the measurement phase is identified by the value of DPMO (Defect per Million Opportunities) and six sigma capabilities. Furthermore, the analyze phase is done by finding the root of the problem using fishbone diagrams and FMEA (Failure Mode and Effect Analysis) to attain the value of RPN (Risk Priority Number) and the highest five RPN values. One out of the five causes that are recommended to be prioritized in the handling is operators do not work according to SOP. Finally, in the improvement phase, the new SOP from the results of discussions / interviews was made with the expert judgment related to the operation of the unloading equipment at TUKS PT. Petrochemical Gresik. By this study, lean six sigma can be applied to minimize the occurrence of demurrage by PT. Petrochemical Gresik and other industrial ports.